Investigating the role of rilmenidine and spermidine on autophagic flux and cell death in a model of Alzheimer's disease - Lumkwana, Dumisile (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.